2000
DOI: 10.1016/s0960-9822(00)00417-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deletion of the Pten tumor suppressor gene promotes cell motility by activation of Rac1 and Cdc42 GTPases

Abstract: Pten (Phosphatase and tensin homolog deleted on chromosome 10) is a recently identified tumor suppressor gene which is deleted or mutated in a variety of primary human cancers and in three cancer predisposition syndromes [1]. Pten regulates apoptosis and cell cycle progression through its phosphatase activity on phosphatidylinositol (PI) 3,4,5-trisphosphate (PI(3,4,5)P(3)), a product of PI 3-kinase [2-5]. Pten has also been implicated in controlling cell migration [6], but the exact mechanism is not very clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
198
3
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(222 citation statements)
references
References 17 publications
(23 reference statements)
18
198
3
2
Order By: Relevance
“…16 Indeed, PTEN deficiency led to increased cell motility in PTEN -/-fibroblasts and reintroducing the PTEN gene reduced the enhanced motility of the cells. 17 PTEN inactivation may lead to a more aggressive and metastatic phenotype and may be directly involved in the progression of endometrial carcinoma.…”
Section: Resultsmentioning
confidence: 99%
“…16 Indeed, PTEN deficiency led to increased cell motility in PTEN -/-fibroblasts and reintroducing the PTEN gene reduced the enhanced motility of the cells. 17 PTEN inactivation may lead to a more aggressive and metastatic phenotype and may be directly involved in the progression of endometrial carcinoma.…”
Section: Resultsmentioning
confidence: 99%
“…This activity has been shown to occur independent of Akt. 26,27 Thus, it may be hypothesized that, in breast cancer, PTEN loss activates the Rho family proteins, leading to increased cell migration and invasion through pathways independent of Akt. Further studies are needed for confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Pten deletion in early neural precursors in vivo caused profound neuronal migration defects (Backman et al, 2001;Kwon et al, 2001;Marino et al, 2002;Fraser et al, 2004;Yue et al, 2005). In mammalian fibroblasts, Pten influences migration by regulation of Rac1 and Cdc42 in a lipid phosphatase-dependent manner (Liliental et al, 2000). However, many studies suggest that the effects of PTEN on migration are independent of lipid phosphatase activity, with one study indicating that the C2 domain was required (Raftopoulou et al, 2004) and another implicating the protein phosphatase activity of PTEN (Leslie et al, 2007).…”
Section: Migration and Invasionmentioning
confidence: 99%
“…It is possible that the effects of PTEN on cell migration in vitro are dependent on experimental conditions. Indeed, studies suggesting that the lipid phosphatase activity of PTEN regulates migration by RAC1 inhibition were performed on fibronectin and mediated by a 5 b 1 integrin (Liliental et al, 2000); however, Dey et al (2008) studied glioma cell migration on vitronectin, which binds a v b 3 integrin, and showed that PTEN's protein phosphatase activity negatively regulated RAC1 indirectly by regulating the activity of the SRC-family kinase, FYN. It has also been suggested that PTEN may regulate cell migration by directly dephosphorylating FAK in the DBTRG-05MG glioblastoma cell line (Tamura et al, 1998); however, other studies have shown that PTEN does not influence FAK phosphorylation in other cell lines (Maier et al, 1999;Jones et al, 2001).…”
Section: Migration and Invasionmentioning
confidence: 99%